Kepemimpinan Transformasional dan Kepemimpinan Transaksional terhadap Kinerja - Peran Mediasi Perilaku Kewarganegaraan Organisasi - Dina Novita; Muhamad Nasrip (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2026)
Background - Leadership is a key determinant of organizational effectiveness. However, there is debate about how specific leadership styles translate into tangible performance, particularly through employee volunteerism, or Organizational Citizenship Behavior (OCB). Understanding this mechanism is crucial for identifying whether behaviors outside formal roles truly contribute to performance outcomes or improve the organization's social climate. Aim - This study examines the influence of transformational and transactional leadership on performance, focusing on the mediating role of Organizational Citizenship Behavior (OCB). Design/Methodology/Approach - This study involved 95 participants selected using a non-probability sampling technique with a saturated (census) sampling approach. Data analysis was conducted using variance-based Structural Equation Modeling (SEM) with the help of SmartPLS 3.3 software to test the hypotheses and validate the research instruments. Findings - The results of this study indicate that transformational leadership and transactional leadership have a positive and significant effect on Organizational Citizenship Behavior (OCB) and employee performance. Transformational leadership has the strongest influence on OCB, indicating that a leader's ability to provide inspiration, motivation, and attention to employees can increase employee voluntary behavior in supporting the organization. In addition, OCB has also been shown to have a positive and significant effect on employee performance. Meanwhile, the mediating role shows that OCB is able to mediate the influence of transformational leadership and transactional leadership on employee performance. This indicates that improving employee performance is not only directly influenced by leadership style, but also through the formation of positive organizational behavior. Research Implications - These results highlight the importance of transformational leadership as a key factor in directly improving organizational performance. The practical implication is that organizations need to prioritize the development of transformational leadership. Furthermore, management needs to understand that encouraging OCB alone is not sufficient to increase formal performance output without alignment with productivity targets. Limitations - This study is limited in terms of the number of variables examined. Future research is recommended to integrate additional variables, such as the work environment, to comprehensively explore other factors that may have a stronger influence on improving employee performance.